A novel cardiac muscle‐derived biomaterial reduces dyskinesia and postinfarct left ventricular remodeling in a mouse model of myocardial infarction. Issue 3 (29th March 2015) - O'Connor, Daniel M.; Naresh, Nivedita K.; Piras, Bryan A.; Xu, Yaqin; Smith, Robert S.; Epstein, Frederick H.; Hossack, John A.; Ogle, Roy C.; French, Brent A.
Abstract: Extracellular matrix (ECM) degradation after myocardial infarction (MI) leaves the myocardium structurally weakened and, as a result, susceptible to early infarct zone dyskinesia and left ventricular (LV) remodeling. While various cellular and biomaterial preparations have been transplanted into the infarct zone in hopes of improving post‐MI LV remodeling, an allogeneic cardiac muscle‐derived ECM extract has yet to be developed and tested in the setting of reperfused MI. We sought to determine the effects of injecting a novel cardiac muscle‐derived ECM into the infarct zone on early dyskinesia and LV remodeling in a mouse model of MI. Cardiac muscle ECM was extracted from frozen mouse heart tissue by a protocol that enriches for basement membrane constituents. The extract was injected into the infarct zone immediately after ischemia/reperfusion injury ( n  = 6). Echocardiography was performed at baseline and at days 2, 7, 14, and 28 post‐MI to assess 3D LV volumes and cardiac function, as compared to infarcted controls ( n  = 9). Early infarct zone dyskinesia was measured on day 2 post‐MI using a novel metric, the dyskinesia index. End‐systolic volume was significantly reduced in the ECM‐treated group compared to controls by day 14. Ejection fraction and stroke volume were also significantly improved in the ECM‐treated group. ECM‐treated hearts showed a significant ( P  < 0.005) reduction in dyskinetic motion on day 2. Thus, using high‐frequency ultrasound, it was shown that treatment with a cardiac‐derived ECM preparation reduced early infarct zone dyskinesia and post‐MI LV remodeling in a mouse model of reperfused MI. Abstract : Extracellular matrix degradation after myocardial infarction leaves the myocardium structurally weakened and susceptible to early infarct zone dyskinesia and left ventricular remodeling. Using high‐frequency ultrasound, this study demonstrates that treatment with a novel cardiac‐derived extracellular matrix preparation reduces early infarct zone dyskinesia and post‐MI LV remodeling in a mouse model of reperfused myocardial infarction.